Comercialización de leche fresca en la asociación de ganaderos 17 de abril en el cantón El Empalme del Guayas. - Macías Anchundia, Cecilia Isabel (2016)
This researchs was carried out with the initiative to initiative to improve the producction of fresh milk, partherns cattlemens association on april 17 bloging to the canton El Empalme, Guayas province. This reserachs had as its main pirpose to analyze the marketing of fresh milk abd seek to stengthen the gathering of the association, as specific objetives: to describe the characteristcs of the marketing..............................................................................................